Quality-Adjusted Life Years and Disability-Adjusted Life Years Are Better With Concurrent Chemoradiation Therapy Than Induction Chemotherapy Followed by Chemoradiation Therapy in Nasopharyngeal Carcinoma - Nittala, Mary R (Cureus, 2021)
Introduction As traditional measures such as overall survival (OS) or disease-free survival (DFS) alone do not give a holistic view of the outcomes of a treatment paradigm, we determine to add the evidence of quality-adjusted life year (QALY) and disability-adjusted life year (DALY) to the outcomes of the nasopharyngeal carcinoma patients (NCP) treated with definitive chemoradiation therapy (chemoRT) with or without induction chemotherapy (induction chemo). Methods This is a retrospective analysis of 85 NCPs treated at an academic state institution. The OS estimated by the Kaplan-Meier method and the multivariate Cox regression model determined the co-variables associated with the OS. The relationship between QALYs gained and DALYs saved were calculated from age of the disease onset, duration of the disease, quality of life (QoL) and disability weights. Results Of the 85 eligible NCPs of this cohort, the disease frequency distribution per the World Health Organization (WHO) classification was 41.2% for Type-I, 42.4% for Type-II, and 16.5% for Type-III. The median follow-up (24 months). The five-year OS of patients treated with concurrent chemoRT vs. induction chemo followed by concurrent chemoRT was 54.7 vs. 14.8% for WHO Type I, 60.1 vs. 58.3% for WHO Type II, and 83.3 vs. 50.0% for WHO Type III (p=0.029). The average DALYs saved with concurrent chemoRT were 12.2 years vs. 5 years for induction chemo followed by concurrent chemoRT. The average QALYs gained with concurrent chemoRT were 6.9 years vs. 3.1 years for induction chemo followed by concurrent chemoRT. Conclusion Patients treated with concurrent chemoRT had an increased QoL when compared to induction chemo followed by concurrent chemoRT. The average DALYs saved were higher in the patients treated with concurrent chemoRT than treated with induction chemo followed by concurrent chemoRT.